Possible Mechanisms Of Action And Inhibition Of Biofilm By Cassia Spectabilis (DC.) Methanol Leaf Extract On Candida Albicans Cells And The Cytotoxicity Effect - Torey, Angeline Torey Ayah (2012)
Candida albicans in its biofilm mode of growth is increasingly attracting interest in its role in human infections due to the development of resistance to commonly-used antibiotics or phenotypic adaptation within the biofilm. Hence, in this study the inhibitory effect of methanol extract of Cassia spectabilis leaves was evaluated against biofilm-forming C. albicans with the mechanisms of action. The leaf extract was first standardized in terms of authenticity, assay and chemical constituent analysis. Then the antifungal activity of the extract against C. albicans was established by using the disk diffusion and minimum inhibitory concentration (MIC) assay using the broth macrodilution method.